The Effect of preoperative cares with holistic approach prior to surgical procedure on the patient's anxiety and fulfillment - Farah Madarshahian; Mohsen Hasanabadi; Soheila Khazaei (Guilan University of Medical Sciences, 2015)
Abstract Introduction: Although integrating the patients needs physically and psychologically within their socio-cultural beliefs during providing cares is the source of holistic nursing, but the effectiveness on the patient s anxiety and fulfillment still unclear. Objective: The objective of this study was to determine the effect of preoperative cares with holistic approach prior to surgical procedure on the patient s anxiety and fulfillment. Methods: In this quasi experimental study 78 patient facing prostate surgeries were selected through convenience sampling method during 2010 at Birjand Emam Reza Hospital and allocated to two groups of 39 patients. The involvements consist of determine patients needs physically, socially, psychologically, religious and cultural such as prevent hospital infection and providing holistic cares prior operation using 5 questions. The control group received routine cares. Data were gathered with the Amsterdam Anxiety Scale and one researcher-developed patients satisfaction questionnaire then were analyzed by descriptive statistics, Chi-square, independent and paired t-tests. Results: Experimental and control groups in relation to age, education and place of residence were similar. After intervention the total mean anxiety score of experimental group (14.30±2.66) was lower than control (15.38±1.51) group (p<0.031). The satisfaction of experimental group (91.15±5.35) was higher than control (80.69±11.89) group (p<0.0001). Conclusion: Preoperative holistic cares for reduction of anxiety and improve satisfaction between patients prior to prostate surgery was efficient. Therefore this procedure could be recommended for anxious patients.